Jenis Burung di Area Reklamasi PT Adaro Indonesia yang Direvegetasi Tahun 1996/1997 - Soendjoto, Mochamad Arief; Riefani, Maulana Khalid; Triwibowo, Didik; Wahyudi, Fazlul (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
The species richness of birds had been documented in an observation period, but this preliminary data was inadequate.Additional data were needed so the result could be utilized as a standard to measure the success of reclamation and revegetation. The aim of the research was to update the species richness of birds inthe ex-coal-mining area reclaimed and revegetatedin 1996/1997 andto compare bird species among observation periods (PP).The birds were observed in 3 PPsthrough observation plot andwalking survey in the habitat type of acasia forest (HA), sengon forest (HS), trembesi forest (HT), mixed forest (HC), shrub - bush (SB), open land â€“ grasses (LTPR), andwaters (PA). Bird status was categorized in accordance with valid regulations. Overall 76 bird species were found, but the number fluctuated in every PP. There were47 species in PP-1,62 in PP-2, and61 in PP-3. Of 76 species, 16 speciesare protected by PP 7/1999; 2 speciesare vulnerable, 3 are near threatened, andothers are least-concern species according to IUCN; 5 speciesare in Appendice II andothers are non-appendiceaccording to CITES; and36speciesare likely to be residents.Species andthe number of birds in the revegetated area of 1996/1997 were not as much as those of the primary (undisturbed) forest, but could be used as a minimumstandard for the other reclamation and revegetationareasin the concession of PT Adaro IndonesiaÂ